파력발전을 위한 파유기 회전수류 유수실의 국내 연안 적용 가능성에 대한 수치해석적 조사 - 최정규(Jung-Kyu Choi); 김형태(Hyoung-Tae Kim) (Han-guk haeyang gonghak hoeji (Online), 2013)
In this paper, a wave-induced swirl water chamber (SWC) for breakwater and wave power generation is introduced and its applicability to wave power generation in the coastal waters of Korea is investigated. The SWC type of wave power generation is a way to drive a turbine using the unidirectional swirl flow that is induced in the back of a curtain wall of a breakwater due to incident waves. The typical wave characteristics are obtained by analyzing the annual statistical wave data from KHOA (Korea Hydrographic and Oceanographic Administration). A numerical analysis is carried out on the variations in the SWC entrance height, wave height, and different installation conditions. For the numerical analysis, a commercial code, Fluent based on FVM, is used. As the entrance height decreases, the mass flow rate through the entrance is rarely changed, whereas the magnitude of the flow velocity of the smaller entrance height is greater than the other ones, which is better for the formation of an SWC swirl flow inside and the flow kinetic energy at the entrance. In cases of installation conditions where a wall is place behind and under SWC, it has been shown that the mass flow rate through the entrance is greater than that in the open condition, and sufficient flow kinetic energy is generated in the entrance for wave power generation. However, the swirl flow kinetic energy is relatively small. Thus, in the future, it is necessary to study the swirl flow generation, which is affected by the SWC shape.